Studi Literatur Review Desain Dan Fluida Kerja Pada Shell And Tube Heat Exchanger - Nor Fajri; Yudistira Anugrahadi Wiraputra; Fredi Insan Nurfadli; Fisika Prasetyo Putra (BULLET : Jurnal Multidisiplin Ilmu, 2026)
Shell and Tube Heat Exchanger s are the most widely used type of heat exchanger in the process, energy, and manufacturing industries due to their structural reliability and operational flexibility. However, various studies show that conventional designs still face limitations in achieving high heat transfer performance with controlled pressure losses. This article aims to critically review approaches to improving the performance of Shell and Tube Heat Exchanger s through design modifications and working fluid selection. The method used a semi-systematic approach to experimental studies, numerical studies, and previous reviews discussing baffle innovations, tube geometry variations, the application of porous media, passive enhancement methods, and the use of nanofluids. The results show that design modifications, particularly to the baffles and tube geometry, can improve heat transfer performance by 20–40% compared to conventional configurations. Passive enhancement and porous media approaches enhance flow mixing and turbulence intensity, but are often accompanied by an increase in pressure loss of up to 15–60%. The use of nanofluids and hybrid nanofluids was reported to improve thermal performance by 25–35%, with the main limitations being increased fluid viscosity and pump power requirements.